Unions and employers' associations in Germany: A survey of their membership, density and bargaining coverage - Claus Schnabel (Journal for Labour Market Research, 2025)
Trade unions and employers' associations play an important role in Germany not only in wage setting, but also in social policy and labour market regulation. While the majority of companies are organised in employers' associations, less than one fifth of employees are still members of a trade union. Union density has declined substantially over the last decades whereas on the employers' side density has fallen to a lesser extent as most employers' associations have introduced the option of bargaining-free membership. At the same time, the collective bargaining coverage of companies and employees has been reduced drastically. Nowadays, less than half of employees in Germany are formally covered by collective agreements. Nevertheless, collective agreements are still directly or indirectly relevant for three out of four employees, and they are an important anchor for wage setting in the entire economy. The erosion of (multi-employer) bargaining coverage has manifold reasons and has been associated with an increased heterogeneity in wage setting over the last decades. The ongoing falls in both bargaining coverage and union density have prompted a controversial discussion of how to stabilise the system of industrial relations in Germany.
Keywords: J51; J52; J53; J58; 330; Bargaining coverage; Collective bargaining; Employers' association; Germany; Trade union